WHEN TO INDICATE RADIOTHERAPY AFTER NIPPLESPARING MASTECTOMY? SYSTEMATIC REVIEW - Lisboa, Fabiana Christina Araújo Pereira; Pereira, Pollyanna Dornelas; Calvano Filho, Carlos Marino Cabral; Carvalho, Thiago Machado Carlos de; Urban, Cícero de Andrade; Amorim, Rivadávio Fernandes Batista de (Mastology, 2018)
Introduction: Nipple-sparing mastectomy (NSM) and preservation of the nipple-areola complex (NAC) represent a therapeutic option of breast cancer with a better aesthetic result, a positive impact on body image and more satisfaction than the reconstruction of the NAC. It is questioned the indication of radiotherapy when the NAC is maintained and its potential aesthetic impairment. Objective: To examine the indication of radiotherapy in NSM and, secondarily, the incidence of NAC involvement and local recurrence rates. Methods: Systematic review carried out in the PubMed database with the terms (“breast neoplasm” [Mesh] OR “breast cancer”) AND (“radiotherapy” OR “radiation therapy”) AND (“nipple sparing mastectomy” OR “mastectomies” OR “subcutaneous mastectomies”). The selection of the studies, the evaluation of its quality and data extraction were carried out independently by four reviewers. Results: The indications for radiotherapy after NSM were: positive axilla, tumors over 5 cm and retroareolar tissue remaining greater than 5 mm. The NAC involvement occurred in 5 to 26.1% in the definitive anatomopathological study. NAC recurrence occurred from 2.59 to 10%. NAC necrosis occurred in 2.2 to 43.4%. Conclusions: The radiotherapy indications for NSM seem to follow the same classical indications for radiotherapy after mastectomy. The relapse index in NAC was not shown to be larger and without difference for the type of radiotherapy used. Radiotherapy should be based on factors that suggest a high risk for NAC involvement.